1980
DOI: 10.1073/pnas.77.3.1516
|View full text |Cite
|
Sign up to set email alerts
|

Classification of cultured mammalian cells by shape analysis and pattern recognition.

Abstract: We have developed a method for classifying cultured cells on the basis of shape characteristics. High-resolution optical information on thre imensional shape was obtained by anodic oxide interferometry. Each interference order formed in a cell was considered as a closed figure; measurement of 37 mathematical descriptors was carried out for each figure. The individual cells were classified according to the values of their descriptors. We used standard principles of pattern recognition, such as hierarchical clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…In general semiquantitative scores obtained by visual inspection of the cells are used. Recently, the area occupied by cells on a substratum has been measured, often by computer assisted planimetry (8,10,12), while a number of mathematical formulations have been developed to quantify cell shape, orientation or polarization (7,11 14) for automated karyotyping was adapted for our purposes. This system has a high accuracy mainly due to the use of scanned photonegatives and the calculation of a local background for each cell.…”
mentioning
confidence: 99%
“…In general semiquantitative scores obtained by visual inspection of the cells are used. Recently, the area occupied by cells on a substratum has been measured, often by computer assisted planimetry (8,10,12), while a number of mathematical formulations have been developed to quantify cell shape, orientation or polarization (7,11 14) for automated karyotyping was adapted for our purposes. This system has a high accuracy mainly due to the use of scanned photonegatives and the calculation of a local background for each cell.…”
mentioning
confidence: 99%
“…Previously, the laboratory developed methods for the unbiased classification of cell features, based on the use of size-invariant measures of shape [8]. Using a standard statistical procedure, we could extract latent factors that correspond to cell features.…”
Section: The Role Of Filopodia and Other Protrusions In Sensing Adhesmentioning
confidence: 99%
“…The cells' edges were traced onto a transparency and scanned into an SGI workstation running under IRIX. This workstation hosted software for the derivation of values for geometric variables and model comparisons, as previously described [8]. At least 30 cells from each zone were analyzed, and the set of variable values was reduced to a smaller number of variables by factor analysis [3].…”
Section: Microscopymentioning
confidence: 99%
“…In early work on classification of cell shape, Olson et al [20] showed how machine learning techniques known at that time, i.e., hierarchical clustering and nearest neighbor analysis, could be used to classify cells into three classes by interpreting various shape descriptors. More recent classification techniques, in particular, support vector machines, have been applied by Han et al [8] to the problem of detecting cell nuclei and by Ruusuvuori et al [23] for classifying rod, spherical and spiral bacteria.…”
Section: Introductionmentioning
confidence: 99%